2011
DOI: 10.1016/j.brs.2010.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychologic effects of neuromodulation techniques for treatment-resistant depression: A review

Abstract: Electroconvulsive therapy (ECT) and ablative neurosurgical procedures are established interventions for treatment-resistant depression (TRD), but their use may be limited in part by neuropsychological adverse effects. Additional neuromodulation strategies are being developed that aim to match or exceed the efficacy of ECT/ablative surgery with a better neurocognitive side effect profile. In this review, we briefly discuss the neurocognitive effects of ECT and ablative neurosurgical procedures, then synthesize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 129 publications
(138 reference statements)
1
57
0
4
Order By: Relevance
“…23 Factors associated with greater cognitive impairment following electroconvulsive therapy include pre-existing cognitive impairment, older age and the use of bilateral electroconvulsive therapy. 24 There are no absolute contraindications to electroconvulsive therapy, and it can be used safely during pregnancy.…”
Section: Box 1: Evidence Used In This Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Factors associated with greater cognitive impairment following electroconvulsive therapy include pre-existing cognitive impairment, older age and the use of bilateral electroconvulsive therapy. 24 There are no absolute contraindications to electroconvulsive therapy, and it can be used safely during pregnancy.…”
Section: Box 1: Evidence Used In This Reviewmentioning
confidence: 99%
“…Most studies have found no immediate or prolonged negative effects of transcranial magnetic stimulation on cognition. 38 A study involving 30 patients with major depressive disorder found that, one week after finishing the course of treatment, cognitive performance remained constant or improved (v. pretreatment) among patients who received transcranial magnetic stimulation to the left dorsolateral prefrontal cortex, while deficits in anterograde memory were observed among patients who underwent right unilateral electroconvulsive therapy. 39 Transcranial magnetic stimulation may produce transient headache or local pain in 30%-40% of patients.…”
mentioning
confidence: 99%
“…In fact, electrical convulsive seizure is clinically performed for severe depression and this therapy showed increase of the proliferation and neuronal differnetiation of hippocampal precursors in a depression model of animals [30][31][32]. For Alzheimer's disease, a previous report showed that transcranial direct current stimulation enhanced aspects of memory performance in both healthy controls and individuals with Alzheimer's disease [33]. However, an operation for electrode insertion is needed, and this is invasive for patients.…”
Section: Long-term Potentiation (Ltp) and Neurogenesismentioning
confidence: 99%
“…Whilst there are studies which have not found adverse effects on cognitive function (Sienaert et al, 2010a), for patients where minimizing retrograde amnesia is a priority, right unilateral electrode placement should be the preferred initial choice, given the accumulated evidence suggesting fewer cognitive side effects (Kellner et al, 2010a;O ' Connor et al, 2010a). Some patient-specifi c factors increase the likelihood of cognitive side effects: increasing age, lower education level, lower pre-morbid IQ and psychotropic medication (Moreines et al, 2011). Where there are concerns about cognition, use of dose titration to determine the minimum effective dose and limiting number and frequency of sessions can help to reduce the frequency and intensity of cognitive side effects.…”
Section: What Are the Side Effects?mentioning
confidence: 99%
“…The neuropsychological effects of MST have recently been reviewed (Moreines et al, 2011). Though studies in humans are based on individual case reports or small (less than 20 participants) groups there is growing evidence that MST is associated with few subjective and objective cognitive side effects (Hoy & Fitzgerald, 2010b;Kayser et al, 2011;Kosel et al, 2003;Lisanby et al, 2003a;Lisanby et al, 2001b), as well as rapid recovery of orientation after treatment compared with ECT (Kirov et al, 2008;White et al, 2006).…”
Section: What Are the Effects On Cognition?mentioning
confidence: 99%